Konstruksi Hukuman Pidana Bagi Pelaku Kekerasan Seksual: Studi Kasus di Indonesia - Yantika, Meri; Padrisan Jamba (Universitas Pahlawan Tuanku Tambusai, 2025)
This paper aims to explore the challenges in enforcing Law Number 12 of 2022 on the Crime of Sexual Violence (UU TPKS) in Indonesia. Through an empirical juridical approach, this research combines analysis of written legal regulations with direct observation of their application in the field. The aim is to evaluate the effectiveness of the TPKS Law in providing justice for victims as well as explore the obstacles faced in its implementation, such as the perception of inadequate justice for victims and the inequality of sanctions for perpetrators of sexual violence. Using data collection methods that include an in-depth literature study, this research aims to provide a comprehensive picture of the real conditions in handling sexual violence cases in Indonesia. The results of the research are expected to provide recommendations for improvements to the implementation of the TPKS Law, including adjustments to sanctions for non-physical sexual violence that better reflect the psychological impact experienced by victims, as well as strengthening the protection of victims' rights during the legal process.